THE MAIN THING IS REPRESENTATIVES OF POLLEN AND SUCCULENT PLANTS AND THEIR IMPORTANCE (Neo Science Peer Reviewed Journal, 2023)
There are honey plants in nature, which are also called nectar plants. Nectar plants are angiosperms where bees collect nectar and pollen, and nectar is produced by special nectar glands located in the corolla or sepals, the wall of the node, or the flowers. Anashu is produced from nectar glands. This article mainly provides information about pollen and nectar plants.